2005
DOI: 10.1080/09546630500424649
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for incomplete excision of squamous cell carcinomas

Abstract: We recommend that in patients with SCCs located in the forehead, temples, periauricular region, ears, cheeks, nose, lips or neck surgeons should commence particular surgical measures to avoid inadequate excisions of the tumors. In particular, surgeons should use wider excisional margins in tumors located in the embryonic fusion planes (e.g. eyelids and naso-labial folds).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…Still, well-differentiated SCCs are also able to metastasize, which underscores that one should not only rely on 1 histological feature regarding prognosis. 19 Previous studies on incomplete SCC excision have not demonstrated a relation between differentiation and reexcision rates, 20,21 or omitted to examine this association. 22 The results of our study indicate poor differentiation was a significant risk factor for incomplete surgical excision.…”
Section: Discussionmentioning
confidence: 97%
“…Still, well-differentiated SCCs are also able to metastasize, which underscores that one should not only rely on 1 histological feature regarding prognosis. 19 Previous studies on incomplete SCC excision have not demonstrated a relation between differentiation and reexcision rates, 20,21 or omitted to examine this association. 22 The results of our study indicate poor differentiation was a significant risk factor for incomplete surgical excision.…”
Section: Discussionmentioning
confidence: 97%
“…27 In a separate internal audit of BCC and SCC excised by dermatologists (excluding MMS) in New Zealand, the incomplete excision rate was 0.56% (9/1615), which is the lowest thus reported. 27 10 Plastic surgeons and registrars, tertiary referral centre 480 6.3 22 Dermatologists, outpatient surgery based in tertiary hospital 117 5.2 23 Head and neck squamous cell carcinoma, maxillofacial unit in two hospitals 227 7.0 24 Tertiary referral centre 63 15.9 25 Plastic surgeons in a university medical centre 369 6.8…”
Section: Discussionmentioning
confidence: 99%
“…560 The other studies assessing incomplete excision were retrospective reviews and in those in which the excision margin was specified, margins between 3 mm and 6 mm were used. 546,553,555,559,562 The highest percentage of incompletely excised tumours were observed after excision of periorbital lesions with a 5-mm margin, with 25% being incompletely excised (95% CI 15.3% to 37.0%). 546 None of the included studies reported SCC specific QoL, cosmetic appearance or adverse event data.…”
Section: Combined Griffiths 2002 544mentioning
confidence: 99%
“…543,548 Incompleteness of surgical excision was reported in 11 studies (comprising 2343 excisions). Overall, the pooled average estimate of incomplete excisions was 8.8% (95% CI 5.3% to 13.0%; I 2 = 89%) 541,544,546,550,553,555,[559][560][561][562][563] (see Appendix 6 and Figure 35). Definitions of incomplete excision within the studies were not consistent.…”
Section: Combined Griffiths 2002 544mentioning
confidence: 99%
See 1 more Smart Citation